Strategy of galvanic corrosion mitigation for Mg alloys - Song, Guang-Ling; Yang, Mingyu (Frontiers in Materials, 2025)
The lightest engineering metal magnesium (Mg) alloys have many potential structural and functional applications. However, due to the intrinsic activity of Mg, Mg alloys are not corrosion-resistant. Particularly the severe galvanic corrosion of Mg alloys in contact with other metals in engineering limits the industrial applications. There is currently no cost-effective solution to this stubborn problem. This short review systematically introduces the strategy of galvanic corrosion mitigation, and briefly summarizes the existing approaches that have been used to reduce the galvanic corrosion damage. It appears that the surface alloying that can convert the surface of a Mg alloy into a passive metal is the most promising technique. Based on the existing results in the area of Mg surface alloying, future research directions are listed at last.